Ethnic minorities in the European Union: An overview - Martin Kahanec; Anzelica Zaiceva; Klaus F. Zimmermann (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
This paper sheds light on the labor market situation of ethnic minorities in the European Union. Facing a serious measurement challenge and lacking adequate data, we apply several measures of ethnicity and examine various data sources as well as secondary evidence. We find significant gaps between ethnic minority and majority populations in terms of labor market outcomes. In particular, ethnic minorities appear to face disproportional difficulties in finding a job. Although experience in the host country improves the status of immigrant minorities, we do not find any clear assimilation of further immigrant generations. Roma people seem to face particularly grave integration barriers in European labor markets.
Keywords: F22; J15; J61; J71; 330; Ethnicity; ethnic minority; migration; unemployment; labor force participation; labor market